Digital Neighborhood Watch: Investigating the Sharing of Camera Data Amongst Neighbors - Brush, A.J.; Jung, Jaeyeon; Mahajan, Ratul; Martinez, Frank (CSCW 2013, 2013)
In a neighborhood watch group, neighbors cooperate to prevent crime by sharing information and alerting police of suspicious activities. We propose a digital neighborhood watch (DNW) in which security cameras of individual homes work together to monitor the neighborhood. DNW could augment neighborhood watch by providing digital evidence of crime, increasing visibility of neighborhood activity, and automatically sending alerts when suspicious events occur. We investigate the appeal of sharing camera data with neighbors through semi-structured interviews with 11 households. Our participants validated the potential of sharing data with neighbors, particularly to provide evidence after an incident. But they also had security and privacy concerns about divulging their cameras’ field of view and giving ongoing access to neighbors. For some participants, these concerns can be alleviated by enabling sharing of processed cameras views that include only the fore-ground activity or only public property (e.g., sidewalks).